Limites e consequências da política de concessão de incentivos tributários em um contexto de crise econômico-financeira no Município de Mossoró/RN - Albuquerque, Fernanda Lucena de (2020)
This paper aims to analyze the legal and financial boundaries, as well as the consequences of tax expenditure in the city of Mossoró-RN concerning IPTU and ISS, the main municipal taxes, between 2009 and 2019, during a period of economic and financial crisis. The study is justified by the need to verify the legitimacy of town’s officers, who frequently adopt the conduct of granting tax deductions or exemptions indiscriminatly to specific groups, even compromising fiscal sustainability, in addition to concede cientificy to Mossoró’s fiscal policy in those last 10 years. This paper also proposes to deepen the extra fiscality and tax expenditure practices theoretical framework regarding to tax expenditure theory; minutely verify tax concessional legislation; discuss the (in) existence of tax repercussions due to the revenue waivers and evaluate other outcomes from taxpayers behavior that impacts city’s economic development. The information was obtained from bibliographic and documentary research, with analisys of the specialized literatura, covering Constitutional Law, Tax Law, Financial Law, Economic Law and Administrative Law. Federal Constitution of 1988, a relevant legislation, was also a data source, specially the Fiscal Responsibility Law – FRL and a variety of municipal acts. Evaluating the effects of tax expenditure as a attempt to prove the hyphotesis raised, municipal files from a database called Integrated Tax Administration System – ITAS were also consulted. It was concluded that city managers repeatedly failed to comply with Public and Financial Law regarding tax expenditures, which engendered numerous lossers to public treasury, and, therefore, to society. There were also omissions from inspection agencies, that haven’t implemented control actions, in order to preserve public interest and the legal system assurance, accordingly to Federal Constitution/1988, and FRL, with the concessive tax policy of incentives. All those facts reveals that principles such as transparency, planning, balance, social participation, control and responsibility have been overlooked, while Mossoró’s public accounts were under those managers’ authority during the time range mentioned above